Gender roles and representations of sexual abuse: how are asymmetrical gender attitudes related to the legitimation of sexual abuse of children and youth? - Monteiro, C.; Moleiro, C. (Vulnerable Children and Youth Studies, 2022)
Sexual abuse of children and youth is considered a public health problem. However, it is still a taboo, surrounded by a variety of myths. The main objective of this work was to investigate the relationship between attitudes toward gender roles and the social representations of sexual abuse of children and youth in a sample of students and professionals in the fields of health, education, social work, law, law enforcement and others with contact with children and youth. The present study consisted of a sample of 168 participants, and data collection was performed through an online questionnaire consisting of three self-report instruments–Questionnaire on Representations of Sexual Abuse of Children–Stories (QRASC-HIS), the Sexual Abuse Beliefs Scale (SABS) and the Pacific Attitudes Towards Gender Scale (PATG). Main findings indicate that attitudes toward gender roles were related to the social representations of sexual abuse of children and youth, in that individuals with more gender asymmetric attitudes reported greater legitimation beliefs of sexual abuse. Data also showed that cases where the aggressor was a female adult and the victim was male (pre-adolescent boy) were more legitimated. Implications for theory, practice and training are discussed.